Oles Honchar’s Sacred World (Linguostylistic Studies, 2015)
The article deals with the evolution of Oles Honchar’s spiritual formation depicted in his diary where he recorded the period of mankind’s ordeal – the Second World War and the post-war period of reconstruction and ideological doctrines of the Soviet State. Religious reflections of a talented writer are expressed in aphorisms, prayers of gratitude, salvation and punishment; forgiveness; synonymous lines which characterize the Creator of the World and God’s Mother; as well as in Christian holidays – Easter, Christmas; in edification and in the images of righteous men. Thinking over the historical events of the 20th century, Oles Honchar uses biblical expressions as the evaluation standard of the justice of the Superior Power in conditions of social development at that time. The writer also uses his own word formations – the Fall of man, deviltry, Doomsday, Jesus-like, holy-evening and others which characterize constantly opposing forces of mankind – the Good and the Evil. Key words: religion, Go, God’s Mother, prayer, faith, synonyms, aphorisms, word combination, temples, religious figures. References